Wireless Multifunctional Surface Acoustic Wave Sensor for Magnetic Field and Temperature Monitoring. Issue 3 (16th October 2021) - Yang, Yang; Mengue, Prince; Mishra, Harshad; Floer, Cécile; Hage‐Ali, Sami; Petit‐Watelot, Sébastien; Lacour, Daniel; Hehn, Michel; Han, Tao; Elmazria, Omar
Abstract: A one‐port surface acoustic wave (SAW) resonator based on Co40 –Fe40 –B20 /SiO2 /ZnO/quartz multilayer structure and exhibiting a dual mode, Rayleigh and Love wave modes, is investigated to achieve a multifunctional sensor measuring both temperatures and magnetic fields. The Rayleigh wave mode of the resonator is used for temperature measurement with a temperature sensitivity of −37.9 ppm/°C, and the Love wave mode is used for magnetic field measurement. Co40 ‐Fe40 ‐B20 is the magnetic sensitive layer, and quartz crystal is the piezoelectric substrate. ZnO film is also a piezoelectric but considered here in combination with SiO2 as insulating layers and serves to control impedance matching and temperature dependence of the sensor. ZnO and SiO2 thicknesses are selected to realize temperature compensation for the Love wave mode and making this mode highly sensitive to magnetic fields and insensitive to temperatures. The magnetic field sensitivities of −170.4 kHz m −1 T −1 and −621.6 kHz m −1 T −1 are obtained respectively for the fundamental and the third harmonic of the Love wave mode. The proposed structure is beneficial to design reliable hybrid SAW magnetic field and temperature sensors. Abstract : A dual mode surface acoustic wave resonator based on Co40‐Fe40‐B20/SiO2/ZnO/quartz multilayered structure operates as a multifunctional sensor. Such a structure combining Love waves and Rayleigh waves allows the wireless measurement of magnetic field intensity and temperature simultaneously and independently. The Rayleigh wave mode with a large temperature coefficient of frequency value (−37.9 ppm/°C) and a low magnetic field sensitivity is used for temperature measurement. The Love wave mode exhibits a high sensitivity to magnetic field intensity (621.6 kHz m −1 T −1 ) and is insensitive to temperature.